DETECTION OF DIARRHEAGENIC ESCHERICHIA COLI IN HUMAN DIARRHEIC STOOL AND DRINKING WATER SAMPLES IN OUAGADOUGOU, BURKINA FASO. - Bonkoungou, Isidore Juste Ouindgueta; Siourimè Somda, Namwin; Traoré, Oumar; Sibiri Zoma, Barthelemy; Garba, Zakaria; Maxime Drabo, Koine; Barro, Nicolas (African Journal of Infectious Diseases (AJID), 2020)
Background: The presence of diarrheagenic Escherichia coli (DEC) in drinking water, is a grave public health problem. This study was aimed at characterization of diarrheagenic Escherichia coli isolated from drinking water and faecal samples from diarrheic patients in Ouagadougou, Burkina Faso. Materials and Methods: A total of 242 water samples consisting of 182 potable sachets and 60 from boreholes were collected in the period between October 2018 and April 2019 in the city of Ouagadougou. Faecal samples were also collected from 201 diarrheic patients visiting National Public Health Laboratory for a biological diagnosis by coproculture. The presence of virulence genes associated with DEC was determined by 16-plex polymerase chain reaction from bacteria culture. Results: From drinking water, we found 17% (42/242) Escherichia coli isolates in which 1% (2/242) DEC were detected. Among analyzed samples (182 sachet water versus 60 borehole water), the two DEC (01 ETEC and 01 EPEC) were detected in sachet water. DEC were detected in 20% (40/201) of patients. Enteroaggregative Escherichia coli (EAEC) were mostly detected in 10% followed by Enteropathogenic Escherichia coli (EPEC) in 4%, Enteroinvasive Escherichia coli (EIEC) in 2%, and Shiga toxin-producing Escherichia coli (STEC) 0.5%. However, Enterotoxigenic Escherichia coli (ETEC) was not detected alone, but in co-infections with EAEC. Conclusion: The present study documented the prevalence of Escherichia coli pathovars associated in patients with diarrhea, and shows that drinking water might be a source of DEC transmission in human.